2013
DOI: 10.4103/1119-3077.110144
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminthiasis and nutritional status of children living in orphanages in Benin City, Nigeria

Abstract: Intestinal helminthiasis is associated with under-weight and stunted growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
1
11
2
1
Order By: Relevance
“…In contrast to the current findings, previous studies of welfare homes in other countries such as Bangladesh, Nigeria, Ghana, and Sri Lanka reported that the prevalence of underweight was higher than that of overweight [37,38,39,40]. Nonetheless, the current findings are in agreement with a study among children living in welfare homes in Southeast Nigeria, wherein the prevalence of overweight (30.0%) was higher than the prevalence of underweight (2.2%) [41].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the current findings, previous studies of welfare homes in other countries such as Bangladesh, Nigeria, Ghana, and Sri Lanka reported that the prevalence of underweight was higher than that of overweight [37,38,39,40]. Nonetheless, the current findings are in agreement with a study among children living in welfare homes in Southeast Nigeria, wherein the prevalence of overweight (30.0%) was higher than the prevalence of underweight (2.2%) [41].…”
Section: Discussioncontrasting
confidence: 99%
“…Severity in intestinal helminths resulted from fluctuation in metabolic rate, anorexia, chronic anemia, obstructing intestinal lumen of children associated with heavy worm-load [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the wide-range morbidity and mortality, intestinal parasitosis (IP) is also associated with malnutrition, anaemia, impaired mental function, impaired verbal ability, physical weakness and low educational achievement in school children [13, 14]. For instance, hookworm infection cause anaemia by increasing blood and iron loss in the intestinal tract [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some other species such as Ascaris lumbricoides, Entamoeba histolytica, Trichuris trichiura, Strongyloides stercoralis and Giardia lamblia have also been found to have great effect on nutritional status due to increased metabolic rate, anorexia and diarrhoea [15, 16]. IPs cause decreased intake or a functional increase in the body’s nutrient requirement by their interference with absorptive surfaces, physical obstruction of intestinal lumen, production of proteolytic substances, and consumption of nutrients intended for the body [14, 17, 18]. …”
Section: Introductionmentioning
confidence: 99%